Observations of wall conditioning by means of boron powder injection in DIII-D H-mode plasmas. (28th September 2020) - Bortolon, A.; Maingi, R.; Nagy, A.; Ren, J.; Duran, J.D.; Maan, A.; Donovan, D.C.; Boedo, J.A.; Rudakov, D.L.; Hyatt, A.W.; Wilks, T.W.; Shafer, M.W.; et al.
Abstract: We report observations from the DIII-D tokamak indicating that boron (B) powder injection in tokamak plasmas improves wall conditions similarly to glow discharge boronization (GDB). Isotopically enriched B powder (B 11 > 95%) was introduced gravitationally in a sequence of H-mode plasma discharges at rates up to ∼160 mg s −1 for durations up to 3 s. Boron injection to cumulative amounts ≤0.1 g appeared to improve wall conditions similarly to boronization, with indications of reduced wall fueling, reduced recycling at the outer strike point and reduced impurity content at breakdown. Post-mortem analysis of graphite samples exposed to far scrape-off layer plasma fluxes during boron injection confirm the formation of a B-C layer, with average surface composition B:C ∼ 1. The results suggest that injecting boron-rich powders in tokamak plasmas can effectively replenish boron films on carbon plasma facing components to improve wall conditions and extend the duration of the beneficial effects of GDB.